The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11233-021-09071-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring service quality at an online university: using PLS-SEM with archival data

Abstract: The aim of this study is to analyze, evaluate and validate the NSE (National Student Enquiry) as a service quality measure helping both higher education institutions (HEIs) and students in their decision making. Every year the Dutch foundation ‘Studiekeuze123’ sends out a survey (the NSE) to collect data on service quality regarding education at HEIs in the Netherlands. We used the 2019 NSE-data from the only e-learning university in the Netherlands, the Open Universiteit (OUNL), containing a sample of 1287 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…The results of recent studies [44] have shown that students' attitudes towards e-learning are positively influenced by certain factors, such as the perceived usefulness of e-learning, self-management of learning and self-efficacy. The data of another research [25] show that the most important factors of students' satisfaction with the quality of services at the level of online education in universities are the content and structure of the study and Professors/Lecturers, followed by academic guidance and counseling, testing and evaluation and the task of study. Similarly, teachers holding managing and administrative roles or positions reported significantly higher scores in the QEM dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of recent studies [44] have shown that students' attitudes towards e-learning are positively influenced by certain factors, such as the perceived usefulness of e-learning, self-management of learning and self-efficacy. The data of another research [25] show that the most important factors of students' satisfaction with the quality of services at the level of online education in universities are the content and structure of the study and Professors/Lecturers, followed by academic guidance and counseling, testing and evaluation and the task of study. Similarly, teachers holding managing and administrative roles or positions reported significantly higher scores in the QEM dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Another integrated model was developed by Schijns [25] to measure the service quality in terms of online education in universities. The authors applied a PLS-SEM analysis on 1287 university students to understand the service quality factors that can affect the students' satisfaction and intention to recommend their institution.…”
Section: Current Perspectives On Education Quality Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Vrijednosti Cronbach alfa koeficijenata mjernih ljestvica kreću se od 0,928 do 0,958, dok su sve vrijednosti korelacija čestica s pripadajućim konstruktom više od preporučene granične vrijednosti od 0,30 (Nunnally, 1967), čime je potvrđena interna konzistentnost te su stoga sve čestice zadržane i bit će analizirane u kontekstu strukturnog i mjernog modela u sljedećoj fazi. Prvim predloženim modelom "OM-KU" kojeg prikazuje shema 32. ispituje se povezanost održivog marketinga i percipirane kvalitete visokoobrazovne usluge kao mjere uspješnosti poslovanja visokog učilišta, u kojem je "održivi marketing visokog učilišta (OM)"definiran kao formativni konstrukt po uzoru na prethodno provedena istraživanja (Jarvis et al, 2003;Abou-Warda, 2014;Lučić, 2020b;Mukif et al, 2020;Sinčić Ćorić et al, 2020), kao i konstrukt "kvalitete usluge (KU)" (prema Sankar, 2018;Gora et al, 2019;Mulyono et al, 2020;Schijns, 2021) sagledana kao mjera uspješnosti poslovanja visokog učilišta te je sukladno navedenom, primjenom PLS-SEM metode provedena analiza procjene strukturnog modela i testirane su postavljene hipoteze.…”
Section: Rezultati Istraživanjaunclassified
“…Wilson y Millar servicio y prestación de servicios en general, experiencias de consumo. Schijns (2021) indica que la calidad de servicio ayuda a tomar mejores decisiones de rendimiento empresarial. Dewi et al (2021) refieren que la fiabilidad viene a ser la confianza que genera un determinado servicio ofertado, además de brindar una cierta seguridad del acceso a este servicio.…”
Section: Cienciaunclassified